Visual Studio Team Foundation Server 2012 : adopting agile software practices : from backlog to continuous feedback - Guckenheimer, Sam, 1956- (Addison-Wesley, 2012)
Use Visual Studio® Team Foundation Server 2012 and Agile Methods to Deliver Higher Value Software Faster This is the definitive guide to applying agile development and modern software engineering practices with Visual Studio Team Foundation Server 2012--Microsoft's complementary Application Lifecycle Management (ALM) platform. Written by the Microsoft Visual Studio product owner and a long-time Team Foundation Server implementation specialist, it focuses on solving real development challenges, systematically eliminating waste, improving transparency, and delivering better software more quickly and painlessly. Coverage includes • Accelerating the "flow of value" to customers, with a transparent backlog, PowerPoint Storyboarding, VS 2012 feedback requests, and a "usability lab" right into your customers' hands • Driving quality upstream to uncover hidden architectural patterns, ensure cleaner code, fix multiple recurring "cloned" bugs at once, ensure the definition of done with continuous integration and deployment in a reliable build process • Eliminating "no repro" bugs with VS 2012's six powerful mechanisms for more accurate fault identification and use of virtualized test environments • Using Scrum or other Agile methods with Process Templates effectively across distributed teams in large organization by automating burndowns and dashboards to identify "early warning signals" of emerging problems with quality or maintainability • Staying in the groove by storing the state of your work and environment with shelvesets, to let you handle interruptions smoothly • Leveraging VS 2012's new support for multiple Microsoft and open source unit testing frameworks in your IDE and continuous integration pipeline • Performing exploratory testing to uncover bugs in surprising places and testing immersive Windows 8 apps • Rapidly improving team development and collaboration with the hosted Team Foundation Service Whatever your development role, this book will help you apply modern software development practices using Visual Studio Team Foundation Server 2012 to focus on what really matters: building software that begins delivering exceptional value sooner and keeps delighting customers far into the future.